Impact of genetic polymorphisms in CYP2C8 and rosiglitazone intake on the urinary excretion of dihydroxyeicosatrienoic acids. (March 2008) - Kirchheiner, Julia; Meineke, Ingolf; Fuhr, Uwe; Rodrííguez-Antona, Cristina; Lebedeva, Elena; Brockmööller, Jüürgen
The cytochrome P450 enzymes CYP2C8, CYP2C9 and CYP2J2 generate 8, 9-, 11, 12-, and 14, 15-epoxyeicosatrienic acid (EET) from arachidonic acid, and these EETs are then hydrolyzed to dihydroxyeicosatrienoic acids (DHET) before excretion into the urine. It is unknown how genetic polymorphisms affect formation of these diuretic, vasodilatory and anti-inflammatory eicosanoids, and whether the CYP2C8 substrate rosiglitazone inhibits their formation.Methods: A panel of 14, 13 and four carriers of the CYP2C8 genotypes *1/*1, *1/*3 and *3/*3, respectively was preselected for this study. Daily morning oral doses of 8 mg rosiglitazone were administered for 15 days. Urine was collected prior to rosiglitazone, and for 24 h after the first and last administration of rosiglitazone. Urinary EETs and DHETs were analyzed by tandem mass spectrometry.Results: Carriers of the high-activity CYP2C8*3 allele had higher excretion of all three DHETs (p  <  0.01 for 11, 12-DHET, p  <  0.05 for 14, 15-DHET), whereas carriers of the low-activity CYP2C8 haplotype C (genotypes GCGA at positions rs2275622, rs7909236, rs1113129 and rs11572080) had lower DHET excretion in urine before and during rosiglitazone. Rosiglitazone intake leads to a decrease in DHET excretion by approximately 10% (p  <  0.02). Urinary excretion of unhydrolyzed EETs was below the limit of quantification of 50 pg/ml in all samples.Conclusion : The data consistently indicate that genetic variation in CYP2C8 moderately modulates-EET formation as reflected in urinary DHET excretion. This might impact cardiovascular functions, and may be one mechanism explaining the influence of CYP polymorphisms on myocardial infarction and hypertension.